Lévinasovo hledání Tváře a homilie Benedikta XVI. - Vik, Dalibor (Lidé města, 2005)
This reflection freely develops the central motif of Lévinas’ essay “Heidegger, Gagarin and us”. Our aim is to stress especially those moments when the irreplaceable experience of ethical dimension of being is demonstrated most dramatically. We place in contrast the urgency, strength and novelty, still contained in the Lévinas’ massage until today, with the homily of Benedikt XVI given on the occasion of his entry into the Papal Office which, for our purposes, we consider to be a certain reflection of the current development trends of the Catholic Church and therefore by extension of the Christian congregation as a whole.